Adoption of ShopeePay Among Indonesian Gen Z Women: A UTAUT-Based Evaluation - Nadilla Anidew; Arista Pratama; Asif Faroqi (bit-Tech, 2025)
This study investigates factors influencing the adoption and utilization of ShopeePay, a digital wallet integrated within the Shopee e-commerce platform, among Generation Z women in Indonesia. Given this demographic group's active engagement in digital transactions, identifying key behavioral factors underlying their adoption of mobile payment technologies is essential. Guided by the Unified Theory of Acceptance and Use of Technology (UTAUT), this research examines core determinants of behavioral intention toward ShopeePay, additionally incorporating trust, perceived security, and network externalities into the analytical framework. Employing a quantitative research methodology, the study utilized an online structured survey involving 160 female respondents aged between 18 and 27 years who actively use ShopeePay. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) through SmartPLS version 4.1.0.9. Findings demonstrate that performance expectancy, social influence, and perceived security significantly and positively affect behavioral intention to adopt ShopeePay. Trust indirectly influences intention through its impact on performance expectancy. Interestingly, effort expectancy and facilitating conditions did not demonstrate significant direct effects on behavioral intention. These results underscore that Gen Z female users prioritize application performance, social recommendations, and perceived safety when selecting digital payment solutions. Practically, these insights inform e-wallet developers and marketing professionals in designing targeted functionalities and marketing strategies aligned with user expectations and digital habits. Moreover, this study contributes to existing academic literature on mobile payment adoption and offers strategic implications for enhancing user acceptance, particularly among young female consumers in Indonesia.